PTPN3 acts as a tumor suppressor and boosts TGF‐β signaling independent of its phosphatase activity - Yuan, Bo; Liu, Jinquan; Cao, Jin; Yu, Yi; Zhang, Hanchenxi; Wang, Fei; Zhu, Yezhang; Xiao, Mu; Liu, Sisi; Ye, Youqiong; Ma, Le; Xu, Dewei; et al. (The EMBO journal, 2019)
TGF‐β controls a variety of cellular functions during development. Abnormal TGF‐β responses are commonly found in human diseases such as cancer, suggesting that TGF‐β signaling must be tightly regulated. Here, we report that protein tyrosine phosphatase non‐receptor 3 (PTPN3) profoundly potentiates TGF‐β signaling independent of its phosphatase activity. PTPN3 stabilizes TGF‐β type I receptor (TβRI) through attenuating the interaction between Smurf2 and TβRI. Consequently, PTPN3 facilitates TGF‐β‐induced R‐Smad phosphorylation, transcriptional responses, and subsequent physiological responses. Importantly, the leucine‐to‐arginine substitution at amino acid residue 232 (L232R) of PTPN3, a frequent mutation found in intrahepatic cholangiocarcinoma (ICC), disables its role in enhancing TGF‐β signaling and abolishes its tumor‐suppressive function. Our findings have revealed a vital role of PTPN3 in regulating TGF‐β signaling during normal physiology and pathogenesis. Synopsis As abnormal TGF‐β responses are linked to human diseases such as cancer, TGF‐β signaling must be tightly regulated. This study uncovers a PTPN3 as regulator of Smurf2 binding to TβRI, a function that is abolished by hepatocarcinoma‐associated mutations. PTPN3 potentiates TGF‐β signaling independent of its phosphatase activity. PTPN3 stabilizes TGF‐β type I receptor by inhibiting its interaction with Smurf2. L232R mutation associated with intrahepatic cholangiocarcinoma interferes with the TGF‐β activatory and tumor suppressive functions of PTPN3. Graphical Abstract A new PTPN3 function as regulator of Smurf2 binding to TβRI is abolished by mutations associated with intrahepatic cholangiocarcinoma.